2021
DOI: 10.1186/s12987-021-00268-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings of typical iNPH imaging signs in asymptomatic subjects with subclinical cognitive decline

Abstract: Background The etiology of idiopathic normal pressure hydrocephalus (iNPH) remains unclear. Little is known about the pre-symptomatic stage. This study aimed to investigate the association of neuropsychological data with iNPH-characteristic imaging changes compared to normal imaging and unspecific atrophy in a healthy population. Methods We extracted data from the community-dwelling Austrian Stroke Prevention Family Study (ASPS-Fam) database (2006–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…Unfortunately, we only had access to TMT B at follow-up. However, another study found that TMT B scores were worse for individuals who later were classi ed as having iNPH [49]. We cannot infer if this would have been the case in our study, but our results at follow-up coincides with other studies showing di culties with shifting in iNPH [20,49].…”
Section: Discussionsupporting
confidence: 70%
“…Unfortunately, we only had access to TMT B at follow-up. However, another study found that TMT B scores were worse for individuals who later were classi ed as having iNPH [49]. We cannot infer if this would have been the case in our study, but our results at follow-up coincides with other studies showing di culties with shifting in iNPH [20,49].…”
Section: Discussionsupporting
confidence: 70%
“…In 113 people who were imaged at baseline and a follow-up 3 to 5 years later, people with idiopathic normal pressure hydrocephalus at follow-up had more WMHs and, despite being asymptomatic, had evidence of subclinical cognitive decline and worse executive function, memory, and Trail-Making Test B scores. 137…”
Section: Brain Healthmentioning
confidence: 99%
“…Unfortunately, we only had access to TMT B at follow-up. However, another study found that TMT B scores were worse for individuals who later were classified as having iNPH [ 49 ]. We cannot infer if this would have been the case in our study, but our results at follow-up coincides with other studies showing difficulties with shifting in iNPH [ 20 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study found that TMT B scores were worse for individuals who later were classified as having iNPH [ 49 ]. We cannot infer if this would have been the case in our study, but our results at follow-up coincides with other studies showing difficulties with shifting in iNPH [ 20 , 49 ].…”
Section: Discussionmentioning
confidence: 99%